Hu’po Anshen Decoction Accelerated Fracture-Healing in a Rat Model of Traumatic Brain Injury Through Activation of PI3K/AKT Pathway - Shen, Jing; Li, Yan-Ze; Yao, Sai; Zhu, Zhou-Wei; Wang, Xiang; Sun, Hui-Hui; Ji, Wei-Feng (Frontiers in Pharmacology, 2022)
Hu’po Anshen decoction (HPASD) is a traditional Chinese medicine formula comprising five herbal medicines for the treatment of concussion and fracture healing, but its pharmacological mechanism is still unclear. Ultra-performance liquid chromatography coupled with quadrupole time of flight mass spectrometry (UPLC/Q-TOF MS) was used to analyze the main active components of HPASD. Rats were randomly assigned to fracture group, fracture combined with traumatic brain injury (TBI) group (FBI) and FBI combined with HPASD treatment group (FBIH). Rats in the FBIH group were given oral doses of HPASD (2.4 g/kg, 4.8 g/kg and 9.6 g/kg) for 14 or 21 consecutive days. The fracture callus formation and fracture sites were determined by radiographic analysis and micron-scale computed tomography (micro-CT) analysis. Hematoxylin and eosin (H&E) staining and a three-point bending test were applied to assess histological lesions and biomechanical properties, respectively. The levels of cytokines-/protein-related to bone formation and differentiation as well as PI3K/AKT pathway-related proteins were determined by Enzyme-linked immunosorbent assay (ELISA), quantitative reverse transcription-polymerase chain reaction (qRT-PCR), or western blot assays, respectively. UPLC-Q/TOF-MS-based serum metabolomic analysis was also performed to investigate the therapeutic effects of HPASD in the treatment of FBI. UPLC/Q-TOF MS analysis showed the chemical components in HPASD, including flavonoids, amino acids, saponins, and phenylpropanoid constituents, etc. HPASD dose-dependently promoted callus formation, increased bone density, improved mechanical parameters and morphological scores, and facilitated the expressions of VEGF, PDGF, bFGF, VEGFA, CoL1A1, RUNX2, BMP2, and Aggrecan, inhibited the expression of MMP13, and activated PI3K/AKT pathway. Metabolomics analysis revealed abnormalities of malate-aspartate shuttle and glucose-alanine. HPASD accelerates fracture healing by promoting bone formation and regulating the malate-aspartate shuttle and glucose-alanine cycle, which might be associated with the activation of the PI3K/AKT pathway.